Panache: a web browser-based viewer for linearized pangenomes - Durant, Éloi; Sabot, François; Conte, Matthieu; Rouard, Mathieu (Oxford University Press, 2021)
Pangenomics evolved since its first applications on bacteria, extending from the study of genes for a given population to the study of all of its sequences available. While multiple methods are being developed to construct pangenomes in eukaryotic species there is still a gap for efficient and user-friendly visualization tools. Emerging graph representations come with their own challenges, and linearity remains a suitable option for user-friendliness.We introduce Panache, a tool for the visualization and exploration of linear representations of gene-based and sequence-based pangenomes. It uses a layout similar to genome browsers to display presence absence variations and additional tracks along a linear axis with a pangenomics perspective.Panache is available at github.com/SouthGreenPlatform/panache under the MIT License.